Production and use of plastinated anatomical specimens as teaching and learning tools in veterinary gross anatomy in the Caribbean - Mohamed, Reda; John, Roger (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Veterinary Anatomy is considered as the backbone subject in the veterinary medicine program. Formalized specimens were not very much accepted by the veterinary students due to their wetness, bad smell and potential harmful effects. Plastination has evolved as a new technique for prolonged preservation of specimens by replacing the water and fat by a curable plastic polymer. Material and methods: The process of plastination involved fixation, dehydration, impregnation and curing. The plastinated specimens were used for teaching and learning of veterinary gross anatomy courses for veterinary students. Results: Plastinated specimens were appreciated by the staff and students as they were odorless, non-toxic and durable, needed less space for storage and they were used in teaching the veterinary anatomy courses. Plastinated specimens were used for studying not only in the dissection hall but also in the lecture room, both individually and in groups. Conclusion: The plastinated specimens were excellent for demonstration but they could not completely replace the traditional dissection because students learn best by exploratory and hands-on dissection. Moreover, the wet specimens provided a more accurate visual representation of the body parts and skills to aid in dealing with actual clinical cases in the future. Therefore, the plastinated and wet specimens were used simultaneously depending on the topic being taught at the time. http://doi.org/10.5455/javar.2018.e245